Stimulasi Guru dalam Perkembangan Kognitif dengan Alat Permainan Edukatif Puzzle pada Anak Usia 5-6 Tahun di PAUD Ceria Kubu Raya - Elisten, Ria; Halida, Halida; Ramadhani, Ariyani (Lembaga Intelektual Muda (LIM) Maluku, 2025)
This study aims to describe and obtain information regarding teacher stimulation in cognitive development using the educational game tool Puzzle for children aged 5-6 years at PAUD Ceria Kubu Raya. The research method used is qualitative descriptive. The researcher's presence in this study is as an observer collecting observational data about the teacher stimulating cognitive skills through playing with the educational game tool Puzzle in early childhood. The participants of this study are children aged 5-6 years in class B2, totaling 5 children, and 1 classroom teacher as a source for interviews. The data collection techniques used in this study are observation, interviews, and documentation. The data analysis conducted includes data collection, data reduction, data presentation, and conclusions. The technique used to examine the validity of the data is source triangulation and technique triangulation. The results of the study through observation, interviews, and documentation show that teachers stimulate cognitive development with educational play tools, specifically puzzles, for children aged 5-6 years at PAUD Ceria Kubu Raya, in accordance with the observed indicators.